2018
DOI: 10.1016/j.bej.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Energy recovery from wastewater microalgae through anaerobic digestion process: Methane potential, continuous reactor operation and modelling aspects

Abstract: A mixture of piggery slurry and algal species (mainly composed of Nannochloropsis limnetica), grown in municipal wastewater, were used as substrates for biogas production. Mono-and co-digestion experiments were performed at batch and continuous reactor operation. The mono-digestion of wastewater microalgae led to the highest methane yield (408 ± 34 NmL/gVS). However, for manure-based biogas plants, a 60:40 v/v piggery slurry to wastewater microalgae ratio in terms of organic matter was identified as the most e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…The lower yield could also be attributed to a high heavy metal content which creates toxic conditions for biomethane production during anaerobic digestion. Tsapekos et al (2018) evaluated the co-digestion of microalgae grown on municipal wastewater and piggery slurry. Results showed how co-digestion improved methane yield (216 mL/g) compared to single digestion of piggery slurry (176 mL/g).…”
Section: Gaseous Biofuelsmentioning
confidence: 99%
“…The lower yield could also be attributed to a high heavy metal content which creates toxic conditions for biomethane production during anaerobic digestion. Tsapekos et al (2018) evaluated the co-digestion of microalgae grown on municipal wastewater and piggery slurry. Results showed how co-digestion improved methane yield (216 mL/g) compared to single digestion of piggery slurry (176 mL/g).…”
Section: Gaseous Biofuelsmentioning
confidence: 99%
“…가축 분뇨의 혐기성 소화를 통한 메탄 생성에 영향을 주는 다양한 영향 인자들에는 반응 기 운전방식, 전처리 방법, pH 조건, 탄소-질소(C/N)비 등 이 포함된다 [5,6]. 가축 분뇨의 혐기성 소화를 위해 기존 연 구에서 사용한 반응기 운전방식은 크게 회분식 반응기와 연 속식 반응기로 나눠볼 수 있다 [7][8][9][10]. 회분식 반응기는 하나 의 반응기에서 지속적인 흐름이나 배출 없이 일정 시간 처리 후 배출시키는 시스템으로 하나의 반응기에서 여러 공정을 진행시킬 수 있는 장점이 있어 소규모 처리에 적합하다.…”
Section: 서 론unclassified
“…As shown above, temperature and pH have a significant impact on AD performance and biogas production. Thus, co-digestion is presented as a suitable technique able to enhance the buffer system, the substrate pH, and free ammonium nitrogen values, allowing a higher methane yield and a more stable process [67,77,78,99,100]. Meneses-Reyes et al showed that increasing the C/N ratio of the substrate by reducing the microalgae ratio provoked an increase in pH, however, the pH of digestate is similar among the different co-digestion ratios studied (7.33-7.51) [41].…”
Section: Effect Of Initial Conditionsmentioning
confidence: 99%